Progressive Muscle Relaxation Effectively Reduces Nausea and Vomiting Postoperative Laparotomic Surgery - Rosidah, Istiqomah; Ta’adi; Dyah, Dina Indarti (Jurnal Kebidanan dan Keperawatan Aisyiyah, 2023)
Nausea and vomiting are unpleasant effects that often occur after surgery. Some efforts to reduce the incidence of postoperative nausea and vomiting can be done with several strategies. Progressive muscle relaxation is a complementary approach to minimize physical and psychological stress. Peppermint aromatherapy by inhalation or inhalation in postoperative patients with general anesthesia can reduce the average frequency of nausea and vomiting. The method used in this research was quasi-experimental with a pre-post-test control group design. The population in this study was 60 postoperative laparotomy patients. The technique used in taking this research sample is a consecutive sampling technique. Data analysis used Wilcoxon and Kruskal-Wallis at α < 5%. In the treatment group, according to the hospital's SPO, there was a difference in the score of nausea and vomiting before or after treatment, but it was not significant, with a p-value of 0.090. Progressive muscle relaxation therapy for 15 minutes can reduce nausea and vomiting scores but not significantly in the intervention group, with a p-value of 0.003. Combination therapy of progressive muscle relaxation and peppermint aromatherapy for 15 minutes is effective and significantly reduces nausea and vomiting scores in the combination group with a p-value of 0.000. There was a significant difference in the nausea and vomiting scores of the three groups. The combination of progressive muscle relaxation and peppermint aromatherapy was effective in reducing postoperative nausea and vomiting compared to other groups with a score of p-value of 0.000.